Along a Continuum: Spirally-woven Beadwork of the Tlingit, Wasco, and Pit River Peoples - Scherer, Alice (DigitalCommons@University of Nebraska - Lincoln, 2018)
This presentation explores the impact of introducing glass beads on the weaving practices of three Pacific Northwest Indigenous groups. Although Native Americans made and used beads of bone, shell, seed, and stone prior to contact with Western European culture, the 18th-century introduction of glass beads brought new elements of sparkle, regularity, and color to native art and inspired creative expressions. Faced with the challenge of integrating these new materials, women turned to familiar basketry techniques for ideas, adapting traditional basket-making methods to weave beads and native-made fibers into bags, caps, straps, and hair ornaments. Visual evidence for this can be seen in the motifs found on 19th-century woven bead work from the Pacific Northwest, which correlate directly to those used by women on their baskets and flat bags. This presentation will provide examples of loose-warp woven beadwork from three Native American tribes in the greater Pacific Northwest: the Tlingit of Southeastern Alaska, who focused more on embroidered beadwork than loose warp weaving; the Wasco of the Columbia River Valley, who wove beads until about 1915 at which point loose warp weaving techniques were gradually replaced by beading “on a frame;” and the Pit River Indians of Northern California, who created some of the most idiosyncratic objects, shaping their tubular bags in unusual ways. Over time, native-made fibers of sinew, Indian hemp, and nettle were replaced by commercially available cotton and linen thread. In addition, standards were influenced by needlework instructors at Indian boarding schools and Anglo imagery came to predominate over ancient basket motifs. Understanding the history of native woven beadwork and its techniques helps us understand the sweep of change in native societies and reveals the choices individual women made as they incorporated unusual materials into their visual lexicon and technical repertoire, creating colorful works to adorn their families and homes.